Development of eco-friendly PVA/Sodium alginate/ carboxymethyl cellulose films enhanced with γ-oryzanol and clove oil as active packaging materials for oily foods preservation - Abubakr S. Sallam; Mohammed S. Sallam; Mohamed Abdin; Mohamed E. Salem; Zhiyong Xie; Xia Fan; Xiaoxiong Zeng (Future Foods)
This study aimed to optimize active ecofriendly packaging materials for oil-rich foods. Due to unsaturated fats, oily products degrade quickly. Herein, composite films were fabricated by blending polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, and clove oil. The resulting matrix was further enriched with varying concentrations of γ-oryzanol (0.1 to 0.4 g/100 mL) to enhance its functional properties. Comprehensive characterization including Fourier-transform infrared spectroscopy, scanning electron microscopy, atomic force microscopy, mechanical testing, and biodegradability analysis revealed that the film containing 0.2 g/100 mL γ-oryzanol exhibited superior homogeneity, mechanical strength, and structural integrity. This formulation significantly improved tensile strength (from 58.2 MPa to 63.96 MPa) and reduced water vapor permeability (from 7.52 × 10⁻⁹ to 5.71 × 10⁻⁹ g·m⁻¹·s⁻¹·Pa⁻¹), indicating enhanced moisture barrier performance. Furthermore, γ-oryzanol-enriched films displayed stronger antioxidant activity than those without active agents. When used to package peanut butter, the optimized film with 0.2 g/100 mL γ-oryzanol extended the shelf life of product by 63 days compared with conventional polyethylene packaging, owing to its effective inhibition of lipid oxidation. These findings demonstrate the promise of γ-oryzanol and clove oil-integrated bio-based films as next-generation active packaging materials for the preservation of lipid-rich foods.